The Impact of an Educational Program on Patient Practices for Safe Use, Storage, and Disposal of Opioids at a Comprehensive Cancer Center. (17th January 2017) - de la Cruz, Maxine; Reddy, Akhila; Balankari, Vishidha; Epner, Margeaux; Frisbee‐Hume, Susan; Wu, Jimin; Liu, Diane; Yennuraialingam, Sriram; Cantu, Hilda; Williams, Janet; Bruera, Eduardo
Abstract : Background: Improper use, storage, and disposal of prescribed opioids can lead to diversion or accidental poisoning. Our previous study showed a large proportion of cancer patients have unsafe opioid practices. Our objective was to determine whether an improvement occurred in the patterns of use, storage, and disposal of opioids among cancer outpatients after the implementation of a patient educational program. Patients and Methods: Our palliative care (PC) clinic provides every patient with educational material (EM) on safe opioid use, storage, and disposal every time they receive an opioid prescription. We prospectively assessed 300 adult cancer outpatients receiving opioids in our PC clinic, who had received the EM, and compared them with 300 patients who had not received the EM. The previously used surveys pertaining to opioid use, storage, and disposal were administered, and demographic information was collected. Sharing or losing their opioids was defined as unsafe use. Results: Patients who received EM were more aware of the proper opioid disposal methods (76% vs. 28%; p ≤ .0001), less likely to share their opioids with someone else (3% vs. 8%; p = .0311), less likely to practice unsafe use of opioids (18% vs. 25%; p = .0344), and more likely to be aware the danger of their opioids when taken by others ( p = .0099). Patients who received the EM were less likely to have unused medication at home (38% vs. 47%; p = .0497) and more likely to keep their medications in a safe place (hidden, 75% vs. 70%; locked, 14% vs. 10%; p = .0025). Conclusion: The use of EM on opioid safety for patients with advanced cancer was associated with improved patient‐reported safe opioid use, storage, and disposal. Abstract : Improper use, storage, and disposal of prescribed opioids can lead to diversion or accidental poisoning. The present study compared 300 adult cancer outpatients receiving opioids who had also received educational material (EM) with 300 patients who had not received EM. The use of EM on opioid safety for patients with advanced cancer was associated with improved patient‐reported safe opioid use, storage, and disposal.